Analisis Korelasi Parameter Oseanografi Terhadap Hasil Tangkapan Jaring Purse Seine di Perairan Kranji, Kecamatan Paciran Kabupaten Lamongan - Nova Elasari; Rizqi Abdi Perdanawati; Mauludiyah Mauludiyah (Jurnal Perikanan dan Kelautan, 2022)
Kranji waters have potential fishing grounds for the development of large marine fisheries. Kranji fishermen often face obstacles in their fishing efforts due to a lack of information about the season and potential fishing areas. The oceanographic factor of the waters can be one of the clues to determining a good catch. The purpose of this study was to determine the condition of the oceanographic parameters of the fishing area, determine the catch rate and determine the correlation of oceanographic parameters to the catch of ring trawlers. The data used in this study were temperature, salinity, depth, current velocity and catch for 10 fishing trips. Oceanographic parameters in the Kranji fishing area for 10 fishing trips were as follows: temperature ranged from 29.9- 31.8°C, water salinity ranged from 29-31.1‰, water depth ranges from 50-70 m and the current velocity ranges from 0.09to 0.34 m/s. The variability of ring trawl production during 10 times of capture found 5 species caught. The variability and composition of purse seine catches were as follows: Tongkol Walang with a percentage of 54.42%, Tongkol Lorek with a percentage of 38.13%, belo fish with a percentage of 6.37%, juwi with a percentage of 0.53%, and the lowest. the percentage is bagong by 0.52%. The correlation of oceanographic parameters with purse seine catches is as follows: Current velocity has the highest correlation value with a correlation coefficient of 0.814. The temperature has a strong category value with a correlation coefficient of 0.756. Salinity has a negative correlation value with a value of -0.658. Depth has a strong category value with a correlation coefficient value of 0.657.